2014
DOI: 10.17795/compreped-15777
|View full text |Cite
|
Sign up to set email alerts
|

Paraclinical Evolutions Regarding Liver and Renal Abnormalities of Kawasaki Disease in the Southeast of Iran

Abstract: Context: Hemolytic uremic syndrome (HUS), being more prevalent in infants and children, is recognized by a triad of acute kidney injury, microangiopathic hemolytic anemia, and thrombocytopenia. It is classified according to the underlying disorders, such as infection, systemic, metabolic disorder, or complement dysregulation. It has a high rate of morbidity and mortality. Many types of treatment, such as conservative management, plasma exchange, regular plasma infusion, and even a new expensive medication, "Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A study has reported that 37% of the patients with KD had a significant rise in the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) while 41% of them had an elevated gamma-glutamyl transferase (GGT) level [105]. Similarly, another study also reported that most children with KD had impaired LFT with raised ALT and/or AST [106]. In a retrospective review that scrutinised the liver function profile among 210 KD children, hypoalbuminemia was prevalent along with high AST and low total protein during the acute KD period [17].…”
Section: Liver Function Test and Lipid Profilementioning
confidence: 99%
“…A study has reported that 37% of the patients with KD had a significant rise in the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) while 41% of them had an elevated gamma-glutamyl transferase (GGT) level [105]. Similarly, another study also reported that most children with KD had impaired LFT with raised ALT and/or AST [106]. In a retrospective review that scrutinised the liver function profile among 210 KD children, hypoalbuminemia was prevalent along with high AST and low total protein during the acute KD period [17].…”
Section: Liver Function Test and Lipid Profilementioning
confidence: 99%
“…In the Sedighi et al study, the percentage of pyuria was 20.2% and the difference from the usual frequency, which is usually found in 33-63% of patients, might be explained by the fact that pyuria is a transient symptom and urine analysis should be repeated in suspected patients (2)(3)(4).…”
Section: Dear Editormentioning
confidence: 87%
“…Diagnosis is based on clinical criteria mostly from the affected skin and mucosa (1). It was very interesting that Sedighi et al and Soleimani et al in their recent publications in the Journal of Comprehensive Pediatrics revealed the clinical characteristics of Kawasaki disease, and the liver and renal paraclinical abnormalities, respectively, of this condition in the Iranian population (2,3).…”
Section: Dear Editormentioning
confidence: 99%
“…In patients presenting with febrile cholestatic jaundice, a high index of suspicion to KD should always be maintained (10). Soleimani et al also reported hydrops of gallbladder in 12.7% of the enrolled patients (8). Abnormal gallbladder findings were significantly more frequent in children who developed CAA (11); but, further studies are needed to clarify whether patients with hydrops of gallbladder may require a more aggressive therapy, for example corticosteroids.…”
mentioning
confidence: 99%
“…Recently, two studies evaluated the clinical and biochemical characteristics of KD in Iranian children (8,9). Soleimani et al reported a significant prevalence of liver abnormalities (46.8%), ranging from mild asymptomatic increase in the liver enzymes to severe cholestatic hepatitis (8). In patients presenting with febrile cholestatic jaundice, a high index of suspicion to KD should always be maintained (10).…”
mentioning
confidence: 99%